Incorporating Hope and Positivity Into Educational Policy. (October 2019) - Dixson, Dante D.
American students are underachieving relative to the nation's investment in education. One explanation may be the lack of hope and positivity within America's educational policies. These constructs predict student achievement and improved outcomes in several crisis areas that current educational policy has neglected (e.g., student mental health and school disciplinary practices). Moreover, educational policy can easily incorporate hope and positivity. First, schools can leverage several already-developed, effective, and scalable hope and positivity-based interventions. Second, educational policy can target hope and positivity-based constructs (e.g., student well-being) or incorporate their principles (e.g., focusing on student strengths) in education policy directed at solving problems. Given the evidence, policymakers should leverage hope and positivity in future educational policy.